Identifikasi Mikroorganisme di Lingkungan Pada Udara Dalam Laboratorium Mikrobiologi - Wahidjah Azzizul Asri; Siti Fatimah; Iva Nur Hapsari; Yovano Primandika Rifansaputra; Liss Dyah Dewi A (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The quality of microorganisms in the air describes the health condition of the microbiology laboratory environment and its pathogenicity can cause infections in humans, such as infections of bacteria in the microbiology laboratory. Microscopic identification by observation directly use the colony counter. Pay attention to the shape of the bacteria and count the number of bacteria that grow, after that document the results obtained in the research and analyze them using descriptive analysis. The air quality in the laboratory is a sign of whether the air in the indoor area is good or bad. There are several types of microorganisms contained in the air, there are types of microorganisms that are often found in the air, including bacteria, fungi and viruses. Factors that can influence the presence of microorganisms in the air consist of temperature, air flow, humidity, lighting and the type of microorganism itself. In this study, samples were taken at a central point in the microbiology laboratory, and the results did not show any bacterial growth, so the air quality met laboratory standards. The absence of living microbes in a laboratory area is caused by sterile conditions and the sterilization process.